Health-related quality of life in adolescents with persistent pain and the mediating role of self-efficacy: a cross-sectional study - Grasaas, Erik (Health Qual Life Outcomes, 2020)
BACKGROUND: Persistent pain has a high prevalence among adolescents. Pain has been shown to reduce all aspects of the adolescent’s health-related quality of life (HRQOL). In adult patients with pain, self-efficacy has been shown to mediate the relationship between pain intensity, disability and depression. However, little is known about whether self-efficacy acts as a mediating variable in the relationship between persistent pain and HRQOL sub-scale scores in a school-based population of adolescents. OBJECTIVES: To describe the experience of pain, HRQOL and self-efficacy, and to explore the association between pain intensity, general self-efficacy and HRQOL in adolescents with persistent pain by testing self-efficacy as a possible mediator. METHODS: The study participants were 78 adolescents with persistent pain, aged 16–19 years, who were recruited from five high schools in southern Norway. All participants completed an electronic survey consisting of the Lubeck Pain Questionnaire, which included a visual analogue scale (VAS) measuring pain intensity, the General Self-Efficacy Scale (GSE) and the KIDSCREEN-52 Questionnaire measuring HRQOL. Statistical analyses were conducted using the PROCESS macro for SPSS developed by Andrew Hayes. RESULTS: All participants reported pain in multiple locations, of which the head was most common (88.5%). Mean (SD) pain intensity score of the participants was 5.4 (1.8). The study sample had poor HRQOL, with mean (SD) scores for several sub-scales ranging from 45.2 (21.0) to 91.0 (13.3) on a 0–100 scale. The associations between pain intensity and the HRQOL sub-scales of physical well-being, psychological well-being, mood, self-perception, autonomy and school environment were mediated by self-efficacy. The highest degree of mediation and, thus, the largest indirect effect was estimated for the HRQOL sub-scale physical well-being (67.2%). CONCLUSIONS: This school-based sample of adolescents with persistent pain had impaired HRQOL. Up to 67% of the reduction in the HRQOL sub-scale scores for physical well-being, psychological well-being, mood, self-perception, autonomy and school environment could be explained by the mediating variable self-efficacy. Thus, future pain-management interventions that aim to increase HRQOL in school-based populations of adolescents with persistent pain should consider promoting self-efficacy and providing more targeted interventions. TRIAL REGISTRATION: ClinicalTrials.gov ID NCT03551977.